The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/environments8120133
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Recovery from Digestate Using Gas-Permeable Membranes: A Pilot-Scale Study

Abstract: The reduction and recovery of nitrogen (N) from anaerobically digested manure (digestate) is desirable to mitigate N-related emissions, mainly ammonia and nitrate, derived from digestate land application in nutrient-saturated zones. This work reports the results of a gas-permeable membrane (GPM) pilot-scale plant to recover ammonia from digestate in the framework of the EU project Ammonia Trapping. The total ammonia nitrogen (TAN) concentration in digestate was reduced by 34.2% on average (range 9.4–57.4%). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Comparing the values obtained with those reported in the literature, the NH 3 capture efficiencies for sulfuric, phosphoric, and nitric acid obtained in this study were similar to those attained by other authors [40,45], and the differences may be attributed to the fact that the capture system was not the same. Riaño et al [50], using a submerged GPM system with a sulfuric acid capture solution, reported capture efficiencies of up to 79.7%; Zhang et al [45], using a CapAmm system, obtained NH 3 capture efficiencies of 75% for phosphoric acid and 73% for sulfuric acid; and Reig et al [40], using hollow fiber liquid-liquid membrane contactors (HF-LLMC) combined with ion exchange, attained NH 3 capture efficiencies of 74% and 85% with nitric and phosphoric acid, respectively.…”
Section: Differences In Nh 3 Flux Nh 3 -N Capture and Nh 3 -N Removal...mentioning
confidence: 99%
“…Comparing the values obtained with those reported in the literature, the NH 3 capture efficiencies for sulfuric, phosphoric, and nitric acid obtained in this study were similar to those attained by other authors [40,45], and the differences may be attributed to the fact that the capture system was not the same. Riaño et al [50], using a submerged GPM system with a sulfuric acid capture solution, reported capture efficiencies of up to 79.7%; Zhang et al [45], using a CapAmm system, obtained NH 3 capture efficiencies of 75% for phosphoric acid and 73% for sulfuric acid; and Reig et al [40], using hollow fiber liquid-liquid membrane contactors (HF-LLMC) combined with ion exchange, attained NH 3 capture efficiencies of 74% and 85% with nitric and phosphoric acid, respectively.…”
Section: Differences In Nh 3 Flux Nh 3 -N Capture and Nh 3 -N Removal...mentioning
confidence: 99%
“…Digestate samples from the vessels and acidic solution samples from the acid tank were collected daily to monitor pH and total ammonia nitrogen (TAN). In addition, initial and final samples from the digestate were taken to determine total solid (TS), volatile solid Experimental set-up of the gas-permeable membrane system, consisting of 1 a wastewater vessel, 2 a tubular membrane submerged in the wastewater, 3 a tank containing the acidic trapping solution, 4 a peristaltic pump that continuously recirculated the acidic solution through the tubular membrane, 5 an air pump to supply air to wastewater, and 6 an airflow meter to control the supplied airflow rate.…”
Section: Experimental Procedures For N Extractionmentioning
confidence: 99%
“…For that, air stripping can present high requirements of energy and chemicals compared with the GPM technology. This technology has been successfully proved to recover NH 3 from digestate at pilot scale [3]. Now, the Life Green Ammonia aims at scaling results to the livestock sector market by means of commercial models.…”
Section: Agronomic Assessment Of the N Recovery Solutionmentioning
confidence: 99%
See 2 more Smart Citations